Upaya Meningkatkan Kemampuan Kognitifmelalui Media Kartu Angka Pada Anak Didik Kelompok A Semester I Di Tk Pertiwi Sambiroto Kunduran Kabupaten Blora Tahun2015 / 2016 - SUDARNI, SUDARNI; , Drs. M. Yahya, M.Si (2015)
SUDARNI NIM : A53I130035 Efforts to improve cognitive abilities through the media card numbers on a group of students in kindergarten Pertiwi Sambiroto Kunduran Blora. Thesis PG-PAUD the Faculty of Education, University of Muhammadiyah Surakarta, September 2015. The development of early childhood education could include cognitive development. Ability to be provided for early childhood is the beginning of the cuonting progress through the game card numbers. This study aims to improve the numeracy skills of children in group A in TK Pertiwi Sambiroto Kunduran Blora. The Study, obtained before the improvement was held class (prasiklus) the child is able or completed by ( 29,53%), children who have not been able to 57,81%. Having held research increased in the first cycle of the child who is able to accomplish the task without the help of rising to 86,40%, children who have not been able to complete tasks 80% the result exceeds the indicators of success